Besaran Biaya Bangunan Baru Rumah Tinggal Tipe Sederhana pada Kabupaten dan Kota di Wilayah Pulau Papua Tahun 2024 - Santoso; Nugroho, Aryanto Dwi (Melati Institute, 2024)
Currently, in general, the Papua Island region is experiencing economic growth. This region is divided into 6 provinces, namely: Papua, West Papua, Central Papua, Mountainous Papua, Southwest Papua and South Papua. Based on the 2023 Consumer Price Index (CPI) data, several districts and cities have varying CPIs which illustrate the differences in economic conditions between these regions. These differences in conditions prompted this research to determine variations in the cost of building residential houses. The main objective of this study is to analyze the amount of new building costs for simple residential houses in regencies and cities in the Papua Island region. Using descriptive statistical analysis tools, this study describes building specifications including area and building materials, as well as the amount of new building costs for simple type residential houses. The results of this study conclude that the cost of building a simple type of residential house with a building area of 36 square meters in the Papua Island region in 2024 is statistically, on average, Rp224,854,690.00 (ceteris paribus).